Collection and marketing of high value medicinal and aromatic plants from district Swat, Pakistan - Sher, Hassan (International Food Policy Research Institute, 2013)
The focus of the study was on the collection pattern of medicinal plants as an economic activity within District Swat and the likely destinations of these products in national or international markets. Local collectors/farmers and dealers were surveyed about their collection efforts, quantities collected, prices received, and resulting incomes. Herbal markets in major cities of Pakistan were surveyed for current market trends, domestic sources of supply, imports and exports of herbal material, price patterns, and market product-quality requirements